Saffron (Crocus sativus) production and processing - Kafi, M. (Science Publishers, 2006)
Saffron is a precious spice which is mainly grown in Iran, India, Spain, Greece, Italy, Pakistan, Morocco, and central Asian countries. Until recently, saffron was perceived only for its value as a spice. However, with recent research findings pointing to the medicinal properties of saffron such as its antimicrobial, anticarcinogenic and antioxidant effects, interest in this plant has increased. The book presents a comprehensive account of saffron which includes the historical background, acerage underproduction, yield and applications, botanical ecophysiology, production technology, irrigation, pests, diseases and weeds, genetics, sterility, reproduction and production of secondary metabolites by in vitro method, economic aspects, indigenous knowledge in saffron production, processing, chemical composition and quality control, and research strategies.